Comparison of Ultrasound and MRI in Detecting Breast Cancer: A Retrospective Study in Mumbai Hospitals, India - Singh, Rajendra; Aneel Kumar (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Breast cancer is the most common cancer in women throughout the world. Early detection of breast cancer is very important to increase the chances of cure. Ultrasonography (USG) and magnetic resonance imaging (MRI) are two imaging methods commonly used to detect breast cancer. The aim of this study was to compare the accuracy of ultrasound and MRI in detecting breast cancer in female patients at Mumbai Hospital, India. Methods: A retrospective study was conducted on 2435 female patients who underwent ultrasound and MRI examinations at Mumbai Hospital, India between 2018 and 2023. Patient data was collected from electronic medical records and analyzed to compare the accuracy of ultrasound and MRI in detecting breast cancer. Results: The research results show that MRI is more accurate than ultrasound in detecting breast cancer. MRI sensitivity was 95.2%, while ultrasound sensitivity was 78.3%. The specificity of MRI was 98.7%, while the specificity of USG was 94.3%. The positive predictive value of MRI was 95.2%, while the positive predictive value of USG was 87.5%. The negative predictive value of MRI was 98.7%, while the negative predictive value of USG was 94.3%. Conclusion: MRI is recommended as the primary imaging method for detecting breast cancer in female patients. Ultrasound can be used as a complementary method to MRI.